2007
DOI: 10.1007/s11232-007-0076-2
|View full text |Cite
|
Sign up to set email alerts
|

Metric fluctuations, entropy, and the Wheeler-deWitt equation

Abstract: Quantization using quantum potentials is described in terms of momentum fluctuations, and it is related to Fisher information and entropy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 43 publications
0
13
0
Order By: Relevance
“…( 29) is manifestly scale-invariant, the same must be true for the right hand side, in particular the energymomentum tensor Maeder 2017a), that is, Tµν = T µν . The stress tensor, in general, contains two terms (Carroll 2007) Tµν = T (M)…”
Section: Extension To Cosmologymentioning
confidence: 99%
See 1 more Smart Citation
“…( 29) is manifestly scale-invariant, the same must be true for the right hand side, in particular the energymomentum tensor Maeder 2017a), that is, Tµν = T µν . The stress tensor, in general, contains two terms (Carroll 2007) Tµν = T (M)…”
Section: Extension To Cosmologymentioning
confidence: 99%
“…Experiments have also demonstrated that the Corresponding author: G. Gregori gianluca.gregori@physics.ox.ac.uk de Broglie-Bohm trajectories can have a sound physical interpretation if full non-locality is accounted for (Mahler et al 2016). Extensions to quantum fluids (Haas 2011;Cross et al 2014), field theory (Dürr et al 2004;Carroll 2007) and curved space-time (Dürr et al 2014;Holland 1992;Shojai and Shojai 2006) have also been presented.…”
Section: Introductionmentioning
confidence: 96%
“…e.g. the books and collective volumes) in [3][4][5][6][7][8][9][10][11][12], and individual papers, [34][35][36][37][38][39][40][41][42][43][44][45][46][47][48].…”
Section: G H H H H H H Hmentioning
confidence: 99%
“…[15,16,17,27,34,39,45,49,50,51] and Section 3). There is also a gravitational version of this related to the Wheeler-deWitt (WDW) framework in the form (2.12) [16,17,21,34,51]) and see also [40,92] for WDW). We note also the Perelman entropy functional (2.13)…”
Section: Remarks On Cosmologymentioning
confidence: 99%